ANALISIS PENGARUH INKLUSI KEUANGAN TERHADAP TINGKAT KEMISKINAN DAN KETIMPANGAN PENDAPATAN MASYARAKAT DI KABUPATEN/KOTA PROVINSI BALI - Kusuma, Anak Agung Ngurah Jaya; Indrajaya, I Gusti Bagus (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 9 No 5 (2020): VOL 9 NO 5, MEI 2020, PP 963 - 1199, 2020)
Financial inclusion (financial inclusion) as all efforts aimed at eliminating all forms of price and non-price barriers to public access in utilizing financial services. This study aims to analyze the effect of financial inclusion on the level of poverty and income inequality in the District / City of Bali Province. This study uses secondary data from 2014 to 2018 with research sites in 9 city districts in Bali Province. Path analysis and sobel test are used to determine the direct effect and indirect effect through intervening variables between independent variables in influencing the dependent variable. The analysis showed that financial inclusion had a negative and significant effect on poverty levels. The level of poverty has a positive and significant effect on income inequality. However, financial inclusion has no significant effect on income inequality. This is due to the development of the banking industry in the province of Bali which is still uneven and concentrated in South Bali. Financial inclusion has an indirect effect on community income inequality through poverty levels.   keyword : financial inclusion, level of poverty, income inequality